PERILAKU MASYARAKAT TERHADAP PENYIMPANAN ARSIP KELUARGA - Eritrina Putri Ekantari; Rina Rakhmawati; Titi Susanti (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2022)
The family is the first organization where a person socializes and gets education. In one family creates an archive of everyone in the family. The archives produced in a family are important documents in the phase of human life, ranging from marriage certificates, birth certificates, family cards, and other documents. Maintenance of archival documents in a family is an important thing that must be done, to maintain the integrity of the documents and information contained therein. In rural communities, the management and maintenance of family records is still very minimal in information, so it is not uncommon for family records to be neglected and lost, due to the lack of awareness of family members to maintain their archives. The focus of the research in this study is to look at how to manage digital-based family records and the factors that influence the management of digital-based family records. The method used in this research is a case study. Data were obtained from surveys and literature studies. The results of this study can be seen that people in Indonesia are not fully aware of backing up data from their family archives to anticipate the risk of loss or damage to archives.